2013
DOI: 10.1093/fampra/cmt012
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of multi-morbidity in family practice--issues and biases

Abstract: Background.As the population ages, practice and policy need to be guided by accurate estimates of chronic disease burden in primary care.Objective.To produce a preliminary set of methodological considerations for cross-sectional and retrospective cohort studies of multi-morbidity in primary care using three studies as examples. Prevalence rate results from the three studies were re-estimated using identical age–sex groups.Methods.We compared the methods and results of three separate studies in primary care: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 8 publications
1
35
1
1
Order By: Relevance
“…that are included in the goal/incentive contracts of Catalan PHCTs. Another aspect is the definition and counting of the chronic conditions included, which could modify the results as showen in previous studies [22, 23]. Finally, residual confounding cannot be completely excluded; certain epidemiological factors or other health determinants were not considered in this study, such as environmental factors.…”
Section: Discussionmentioning
confidence: 98%
“…that are included in the goal/incentive contracts of Catalan PHCTs. Another aspect is the definition and counting of the chronic conditions included, which could modify the results as showen in previous studies [22, 23]. Finally, residual confounding cannot be completely excluded; certain epidemiological factors or other health determinants were not considered in this study, such as environmental factors.…”
Section: Discussionmentioning
confidence: 98%
“…5 There is also marked variation in the methodology of multimorbidity studies with respect to the type of data used, the population studied, and the types of chronic diseases included in the pool of multimorbidity. 6,7 A recent comparison of three studies found that the prevalence levels of multimorbidity in a PHC setting ranged from 34% to 95%. 6 Persistent heterogeneity hinders comparability across studies and limits the ability to make informed health system and health policy decisions.…”
Section: (1) Defining and Measuring Multimorbiditymentioning
confidence: 99%
“…6,7 A recent comparison of three studies found that the prevalence levels of multimorbidity in a PHC setting ranged from 34% to 95%. 6 Persistent heterogeneity hinders comparability across studies and limits the ability to make informed health system and health policy decisions. 6,7 Consequently, an explicit and unified methodology to examine multimorbidity in PHC research is needed.…”
Section: (1) Defining and Measuring Multimorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…A review comparing the prevalence of multiple conditions in primary care from three different studies, found the prevalence rates differed by as much as 61% (80). Despite this, it is widely agreed the number of conditions co-occurring in an individual generally increases with age (5,76,79,(81)(82)(83)(84)(85)(86)(87).…”
Section: Prevalence and Impactmentioning
confidence: 99%